Business in the Qur’an and Sunnah: its importance and guideline, special focus on the successful businessmen and businesswomen among Sahabah and Tabi'in - Samsudin, Sofiah (s.n, 2012)
Islamic history has given us undeniable proof on the contributions of the Muslims to the welfare of the public, achieving honour and economic prosperity in this worldly life, governed by the Qur'an and the Sunnah. Today, the situation has shifted, where the deviation of Muslims from Islamic teachings is a direct cause of their decline.